Sistem Pengukuran Tingkat Kekeruhan Air (Turbidity) Dengan Metode Spektrofotometri - Astuti, Erviana Widia; Izzatul Hasanah; Albertini Magdalena Sitorus; Nurul Fatma Hidayati (Journal of Electronics and Instrumentation, 2024)
Understanding water turbidity is crucial for water supply, aquatic ecosystems, and water resource management. Poor water quality can harm human health and the environment. Testing water turbidity in water treatment is important. Turbidity reflects the optical properties of water influenced by suspended solids. Conventional methods, such as turbidimeters, are considered expensive for large-scale measurements. The development of a simple method using spectrophotometry is important as it can measure turbidity using light absorbed and emitted by substances in water. This research aims to determine the relationship between variations in illumination angles and turbidity values of each solution to light intensity and resistance. Spectrophotometry is an experimental method to measure water turbidity based on light passing through a solution with varied illumination angles (0^0, 45^0, 90^0). This study was conducted with three samples of mixed water solutions (50 ml) and soil treated with turbidity variations (10 g, 20 g, 30 g of soil). Turbidity values were calculated based on the sensitivity equation of the SEN0198 sensor. Linear regression analysis was performed to analyze the relationship between solution scattering angles and turbidity with the ratio of initial to final light intensity (I/I_0) and the resulting resistance. The obtained results are the turbidity of solutions 1, 2, and 3, respectively, are 59.590 NTU; 116.879 NTU, and 157.432 NTU. The light intensity ratio (I/I_0) of solution 1 at angles (0^0, 45^0, 90^0) is 0.147; 0.121; and 0.031, and the resistances are 20.8; 24.5; and 58.6 KΩ. The light intensity ratio (I/I_0) of solution 2 at the same angles is 0.147; 0.076; and 0.045, and the resistances are 22.5; 38.4; and 43.2 KΩ. Solution 3 has I/I_0 at the same angles successively 0.040; 0.027; and 0.022, and resistances of 54.2; 62; 63 KΩ. Therefore, the variation in illumination angles is inversely proportional to I/I_0 but directly proportional to resistance in each solution. Additionally, the turbidity values of the solution are inversely proportional to I/I_0 but directly proportional to resistance. The influence of the spectrophotometry measurement system is more significant at a 45^0 illumination angle and in solution 2 with turbidity 116.879 NTU.